Solution processed graphene quantum dots decorated ZnO nanoflowers for mediating photoluminescence - Park, Young Jae; Ko, Kang Bok; Lee, Kyu Seung; Seo, Tae Hoon; Hong, Chang-Hee; Tran Viet Cuong; Son, Dong Ick (ELSEVIER, 2020)
We report the fabrication of hybridization between graphene quantum dots (GQDs) and ZnO nanoflowers (NFs) for mediating photoluminescence by using a straightforward solution-based technique. Hydrothermally grown two-dimensional ZnO NFs played an essential role in assembling GQDs. The large surface area to volume ratio of ZnO NFs led to a highly dense distribution of GQDs, giving rise to photoluminescence (PL) emission at around 442 nm from GQDs and the synergic effects. Thus, GQDs/ZnO hybrid results in strong and broad PL over the spectral range from near UV to red region. We also suggested that an energy interaction between GQDs and various defect sites in ZnO NFs can promote the radiative recombination of both components, thereby providing PL peak intensities more than two times higher than individual components. Fabricated GQDs/ZnO heterojunctions on both soft and hard substrates emit similar intense and wide PL spectrum under ultraviolet irradiation, indicating that this heterojunction can consider as a promising platform for flexible and transparent optoelectronic applications.
Keywords: MICROSPHERES; ARRAYS